The utilization of cowpeas (Vigna unguiculata) and mocaf as ingredients for making pukis with different concentrations of yeast: Pemanfaatan kacang tunggak (Vigna unguiculata) dan mocaf sebagai bahan pembuatan pukis dengan perbedaan konsentrasi ragi - Yessi Yualisa; Vivi Nuraini; Nanik Suhartatik (Agrobiotek, 2025)
Pukis is a traditional cake from Indonesia, made of wheat flour, sugar, eggs, yeast and coconut milk. Cowpeas contains high protein and fiber. Nutrition in cowpea can be used to enrich the nutritional value of pukis. The purpose of this study was to identify characteristics of cowpea flour and mocaf with different yeast concentrations in pukis which are high in protein, fiber and the most preferred by consumers. The experimental design used was a Completely Randomized Design (CRD), the first factor was the ratio of cowpea flour and mocaf (50:50, 70:30, 90:10). The second factor was addition of yeast (2.2; 2.4; and 2.6 g). The analysis indicated that the rasio of cowpea flour to mocaf (50:50, 70:30, 90:10) and the proportion of yeast (2.2; 2.4; and 2.6 g) has a significant effect to chemical analysis of protein, fat, carbohydrate, crude fiber and specific volume, also has a significant effect to sensory tests of color, taste, texture and overall sensory tests. The formulation of pukis which is high in protein, fiber and the most preferred by consumers was found in the ratio of cowpea flour and mocaf 90:10 with the addition of 2.2 g yeast. The best quality of Pukis contain protein 9.12%; fiber 12.75%; moisture content 34.88%; ash content 1.42%; fat 11.45%; carbohydrate 43.14% and specific volume 1.10%. Pukis formulation with the highest level of preference by the panelists has a value of 3.63 (neutral). Pukis from cowpea flour and mocaf with different concentrations of yeast has potency to be a source of protein and dietary fiber.